Serum neopterin levels in the patients of multiple sclerosis - Akbulut, H. Handan; Bulut, Serpil; Berilgen, M. Said; Kansiz, Fatma (Turkiye Klinikleri, 2005)
Objective: Cellular immune system activation functions as a triggering factor in the formation of demyelination plagues in multiple sclerosis (MS). Our aim was to study the levels of neopterin, an important activation marker of the cellular immune response in patients with Relapsing-Remitting MS (RR-MS), during attack and remission periods and to determine its efficacy as a laboratory marker or predictor of imminent periods of disease activation. Material and Methods: 39 age and sex matched healthy patients diagnosed with RR-MS were investigated in the Neurology Department of Firat University Faculty of Medicine. Neopterin levels were determined by ELISA. Patients were classified according to clinical status with the Expanded Disability Status Scale (EDSS). Results: Neopterin levels were 18.77 ± 2.36 nmol/L and 11.79 ± 3.35 ng/mL in the patient and control groups, respectively (p< 0.05). During attack and remission periods, Neopterin levels were 24.42 ± 7.56 mmol/L and 15.95 ± 3.41 nmol/L, respectively (p< 0.01). There was a positive correlation between EDSS scores and neopterin levels of the MS patients (r= 0.4, p< 0.05). Conclusion: We conclude that neopterin levels might be used as an objective criterion in the evaluation of attack periods of RR-MS patients. Copyright © 2005 by Türkiye Klinikleri.
Multipl skleroz hastalarinda serum neopterin düzeyleri
Keywords: Multiple sclerosis; Neopterin